Innovation in Art Material Services at the FIPP UNY Kinanthinastiti Laboratory - Pamungkas, Joko; Anggraeni, Erina Putri (MultiTech Publisher, 2024)
This research aims to analyze innovation in art material services at the Kinanthinastiti Laboratory FIPP UNY. This research uses a descriptive qualitative approach. Starting with conducting secondary data analysis regarding descriptions related to the material and activities that have been carried out at the Kinanthinastiti Laboratory. Data collection techniques were carried out using observation, interviews, and documentation. The research subjects as data sources in this research were students and laboratory assistants at the Kinanthinastiti Laboratory. The art materials that have been applied in the PAUD FIPP UNY laboratory are musical arts, panembromo, wayang anak, new dance creations, traditional dolanan, and innovations in traditional game media.